Targeting innate immunity to downmodulate adaptive immunity and reverse type 1 diabetes - Itoh A; Ridgway WM (ImmunoTargets and Therapy, 2017)
Arata Itoh, William M Ridgway Division of Immunology, Allergy and Rheumatology, University of Cincinnati College of Medicine, Cincinnati, OH, USA Abstract: Type 1 diabetes (T1D) is characterized by specific destruction of pancreatic insulin-producing beta cells accompanied by evidence of beta-cell-directed autoimmunity such as autoreactive T cells and islet autoantibodies (IAAs). Currently, T1D cannot be prevented or reversed in humans. T1D is easy to prevent in the nonobese diabetic (NOD) spontaneous mouse model but reversing new-onset T1D in mice is more difficult. Since the discovery of the T-cell receptor in the 1980s and the subsequent identification of autoreactive T cells directed toward beta-cell antigens (eg, insulin, glutamic acid decarboxylase), the dream of antigen-specific immunotherapy has dominated the field with its promise of specificity and limited side effects. While such approaches have worked in the NOD mouse, however, dozens of human trials have failed. Broader immunosuppressive approaches (originally cyclosporine, subsequently anti-CD3 antibody) have shown partial successes (e.g., prolonged C peptide preservation) but no major therapeutic efficacy or disease reversal. Human prevention trials have failed, despite the ease of such approaches in the NOD mouse. In the past 50 years, the incidence of T1D has increased dramatically, and one explanation is the “hygiene hypothesis”, which suggests that decreased exposure of the innate immune system to environmental immune stimulants (e.g., bacterial products such as Toll-like receptor (TLR) 4-stimulating lipopolysaccharide [LPS]) dramatically affects the adaptive immune system and increases subsequent autoimmunity. We have tested the role of innate immunity in autoimmune T1D by treating acute-onset T1D in NOD mice with anti-TLR4/MD-2 agonistic antibodies and have shown a high rate of disease reversal. The TLR4 antibodies do not directly stimulate T cells but induce tolerogenic antigen-presenting cells (APCs) that mediate decreased adaptive T-cell responses. Here, we review our current knowledge and suggest future prospects for targeting innate immunity in T1D immunotherapy. Keywords: type 1 diabetes, antigen-specific therapy, innate immunity, Toll-like receptors